Semi-regular exercises for the rehabilitation of shoulder joint for weightlifting disabled athletes - Al-Ibraheemi, D. H. E.; Al-Badri, J. Q. M.; Al-Oudah, A. H. O. (Journal of Human Sport & Exercise, 2019)
The weight lifting athletes get injured while they are demonstrating the strength to lift the weight. It is observed mostly the shoulder joints are prone to affect due to physical imbalance or abnormal movement in weightlifting athletes. This results impair normal functional movement. The rehabilitation centers are providing the semi-regular exercises to regain their muscular strength. Muscular endurance is predominant rather than muscular strength. The rehabilitation centers are initially focusing on retain their muscular endurance and then focusing on increasing the muscular strength by practicing the semi-regular exercises. In this research work we suggest the semi-regular exercises to improve 3 different muscle contractions namely isometric contraction, concentric contraction and eccentric contractions of the skeletal muscle. The semi-regular exercises are aiming to improve the joint strength and range of motion in shoulder joint dislocation. This can be provided after two weeks of the shoulder dislocation of the weightlifting athletes with the confirmation from physician. The duration of the semi-regular exercises rehabilitation program is spanned across the period of 6 weeks to regain their muscle power and strength.